Penghargaan dan Sanksi (Studi pada karyawan pelaksana PT. Perkebunan Nusantara IV Unit Kebun Mayang) - Tampubolon, Bob Hans P.; Nugraheni, Rini (Faculty of Economics and Business Diponegoro University, 2013)
Rewards and punishment is one of the main factors that affect employee’s performance.This research focused on the implementation and application of rewards and punishment’s policy within the firm. According to the policy of rewards and punishment for employees at PT. Perkebunan Nusantara IV Unit Kebun Mayang shows that the implementation and application of rewards and punishment sometimes are not applied evenly in accordance with firm’s policy. Generally this is caused by the limited understanding of employees about rewards and punishment at Unit Kebun Mayang, despite the rewards and punishment that has been written in the PKB (Perjanjian Kerja Bersama) PTPN IV within the period of 2012-2013.This study used a qualitative method where the data collection is done by interview and documentation so as to delve deeper into the implementation and application of rewards and punishment. The sample in this research is an active employee who has served for over 10 years and worked at PT. Perkebunan Nusantara IV (Persero) Unit Kebun Mayang.The results obtained from this research stated that the rewards and punishment’s policythat exist in PT. Perkebunan Nusantara IV (Persero) Unit Kebun Mayang has been implemented and applied in accordance to which the rewards and punishment’s policy that are written in the PKB (Perjanjian Kerja Bersama) within the period of 2012-2013. Besides the perceived benefits by active employees of the implementation and application of the award is to make ends meet. Then the purpose of the implementation and application of punishment is to discipline employees. However, there are still some employees that do not know and understand about rewards and punishment thoroughly.